Diversity in the Workplace - Vardy, Felix (IMF Working Papers; Working Paper, 2006)
We study a model where an employer, trying to fill a vacancy, engages in optimal sequential search by drawing from two subpopulations of candidates who differ in their "discourse systems": during an interview, a minority candidate with a discourse system not shared with the employer conveys a noisier unbiased signal of ability than does a majority candidate. We show that, when the employer is "selective," minority candidates are underrepresented in the permanent workforce, fired at greater rates, and underrepresented among initial hires, even though the employer has no taste for discrimination and the populations are alike in their average ability. Furthermore, workplace diversity is increased if: (1) the cost of firing is reduced, (2) the cost of interviewing is increased, (3) the opportunity cost of leaving the position unfilled is increased, or (4) the prior probability that a candidate can perform the job is increased. Indeed, if the prior probability is sufficiently high, or the cost of firing sufficiently low, then minority candidates may be overrepresented in the permanent workforce.